A human isogenic iPSC-derived cell line panel identifies major regulators of aberrant astrocyte proliferation in Down syndrome - Keiji Kawatani (Nature Portfolio, 2021)
Keiji Kawatani et al. developed a panel of Down syndrome (DS) isogenic astrocytes derived from iPSCs to observe the consequence of DS on astrocyte precursor proliferation, differentiation, and gene expression. Their results suggest a dose-dependent effect of DYRK1A and PIGP on DS-derived astrocyte precursor proliferation, and represent a valuable resource and cellular model for future DS research.